Analisis Pengelolaan Keuangan Menurut PSAK No 1 Tentang Penyajian Laporan Keuangan Pada PT. Amartha Mikro Fintek Cabang Talang Kelapa Palembang - Ika, Ika; Salmah, Ninin Non Ayu; Hendri, Edduar (Jurnal Media Akuntansi (Mediasi), 2024)
ABSTRACT The Assertion of Monetary Bookkeeping Principles (PSAK) is a manual for bookkeeping strategies that contain the treatment, recording, readiness and show of fiscal summaries. The information that budget reports provide about an organization's financial position, operations, and changes in its financial position is helpful for many customers in making decisions. This study hopes to conclude the presentation of financial plan reports at PT. Amartha Mikro Fintek Talang Kelapa Palembang Branch as well as the report's compatibility with PSAK No. 1. The technique used to examine this examination information is subjective engaging. Data reduction, data presentation, and conclusions are the three stages of this method. The information assortment method utilized in this study is a documentation study. The analysis demonstrates that PT Amartha Mikro Fintek Talang Kelapa Palembang Branch's financial statements do not fully comply with PSAK No. 1. PT Amartha Mikro Fintek Talang Kelapa Palembang Branch only includes two components in its financial statements. Complete budget summaries comprise of six parts of fiscal reports, to be specific the proclamation of monetary position, far reaching pay articulation, explanation of changes in value, proclamation of incomes, notes to budget reports, and articulations of monetary situation toward the start of the period. The results of the calculations indicate that the Financial Position Statement presented is compliant with PSAK No. 1, and that PT Amartha Mikro Fintek Talang Kelapa Palembang Branch's Income Statement is 80 percent compliant with PSAK No. 1. Keywords: PSAK No. 1, Financial Statements. ABSTRAK Penegasan Prinsip Pembukuan Moneter (PSAK) merupakan pedoman strategi pembukuan yang memuat perlakuan, pencatatan, kesiapan dan penyajian ikhtisar fiskal. Banyak orang menggunakan laporan finansial mendapatkan penjelasan mengenai posisi finansial perseroan, performa serta peralihan posisi keuangannya sehingga membantu mereka dalam mengambil keputusan. Tujuan dari penelitiannya adalah guna mendapati apakah laporan finansial PT Amartha Mikro Fintek Talang Kelapa Cabang Palembang sudah selaras melalui PSAK No 1 serta cara penyajiannya. Data penelitiannya dianalisis dengan menggunakan pendekatan deskriptif kualitatif. Strategi ini menggunakan tiga tahap, yaitu penurunan informasi spesifik, penayangan informasi, dan penarikan akhir. Dalam penelitiannya, study dokumentasi dipakai guna menghimpunkan keterangan. Temuan Analisa menunjukkan maka laporan finansial PT Amartha Mikro Fintek Talang Kelapa Cabang Palembang belum seutuhnya selaras melalui PSAK No. 1. PT Amartha Mikro Fintek Talang Kelapa Cabang Palembang cuma mencantumkan dua elemen dalam laporan keuangannya. ringkasan fiskal utuh terdiri atas enam bagian laporan anggaran, khususnya pengumuman posisi moneter, penjelasan lengkap gaji, artikulasi perubahan nilai, penjelasan pendapatan, catatan atas laporan anggaran, dan artikulasi situasi moneter menjelang awal periodenya. Berlandaskan estimasi yang sudah dilaksanakan memastikan maka laporan posisi moneter yang diberikan telah selaras 23,52% melalui PSAK No 1 namun guna Pernyataan Bayar yang diperkenalkan oleh PT Amartha Mikro Fintek Cabang Talang Kelapa Palembang yakni 80% selaras PSAK No.1. Kata kunci: PSAK No 1, Laporan Keuangan.